2019
DOI: 10.1177/1099800419895114
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Underpinnings of Musculoskeletal Pain During Treatment With Aromatase Inhibitors for Breast Cancer: A Biological Pathway Analysis

Abstract: Background: Musculoskeletal pain (MSKP) is the most reported symptom during treatment with aromatase inhibitors (AIs) for breast cancer. The mechanisms underlying MSKP are multidimensional and not well understood. The goals of this biological pathway analysis were to (1) gain an understanding of the genetic variation and biological mechanisms underlying MSKP with AI therapy and (2) identify plausible biological pathways and candidate genes for future investigation. Method: Genes associated with MSKP during AI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…One possible explanation might be that the participants in this study were breast cancer survivors at an early stage and had completed the active anti-cancer treatments including chemotherapy, while pain is more frequent and severe for cancer patients who are at an advanced stage [37]. Besides, the ethnic difference and genetic variations between the two studies (the previous study [36] recruited participants in the USA) might also lead to different study ndings as genetic variation that involved in metabolism of AIs may contribute to the variations in the occurrence and severity of the side effects including joint pain [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation might be that the participants in this study were breast cancer survivors at an early stage and had completed the active anti-cancer treatments including chemotherapy, while pain is more frequent and severe for cancer patients who are at an advanced stage [37]. Besides, the ethnic difference and genetic variations between the two studies (the previous study [36] recruited participants in the USA) might also lead to different study ndings as genetic variation that involved in metabolism of AIs may contribute to the variations in the occurrence and severity of the side effects including joint pain [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recent pharmacogenetics and pharmacogenomics suggested that the genetic and genomic variation at the population level is associated with the drug metabolism of and drug response to AIs, which may contribute to variability in the phenotype (e.g., occurrence, severity) of joint pain [12]. A full understanding of the phenotype and pre-treatment associates of AIs-induced joint pain in breast cancer survivors can contribute to enhanced symptom monitoring and management programmes, as well as more tailored and speci c healthcare services or interventions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen also helps to maintain the integrity of joints by inhibiting the breakdown of the cartilaginous extracellular matrix, as chondrocytes contain E2 receptors. 10 Estrogen also has an anti-inflammatory effect on the body by decreasing the synthesis of inflammatory cytokines such as tumor necrosis factor (TNF)-a and interleukin (IL)-1b, and increased levels of C-reactive protein (CRP), eotaxin, and monocyte chemoattraction protein 1 (MCP-1) have been detected in patients. 11 Magnetic resonance imaging (MRI) studies in women experiencing AIMSS have shown fluid surrounding the flexor sheaths, thickening of the flexor/extensor tendons in the hands, and fluid in the metacarpal joints, suggesting underlying inflammation caused by the medication.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Several risk factors, such as a period less than 5 years from menopause, previous menopausal hormone therapy and/or taxanes-based chemotherapy, obesity, pre-existing arthralgia or osteoarthritis (OA) at the beginning of AIs, were highlighted [4,10]. More recently, genetic factors primarily acting in estrogen pathways have been proposed as possibly linked with AIA [66][67][68][69]. Garcia-Giralt et al [67], in a study on 343 post-menopausal BC women starting AIs therapy, found several SNPs (rs4919686, rs4919683, rs4919687, rs3781287, rs10786712, rs6163) in the CYP17A1 (a gene encoding for the enzymes involved in the biosynthesis of androgens), as correlated with the onset of AIA after 12 months of therapy.…”
Section: Etiopathophysiology Of Ai-associated Arthralgiamentioning
confidence: 99%